Typhonium flagelliforme decreases protein expression in murine breast cancer - Chodidjah Chodidjah; Taufiqurrahman Nasihun; Eni Widayati (Universa Medicina, 2014)
BACKGROUND Breast cancer treatment is still ineffective, having also various side effects. Breast cancer growth is affected by human epidermal growth factor receptor 2 (HER2/neu) and B cell lymphoma 2 (BCL2) expression. In vitro studies on continuous culture of continuous culture of human lymphoblasts (CEMs) showed that Typhonium flagelliforme (TF) increases apoptosis. The objective of this study was to evaluate whether TF syrup (TFS) could decrease HER2/ neu and BCL2 expression as well as breast cancer volume (BCV) in mice. METHODS An experimental post-test only control group design was conducted on 18 C3H mice with breast cancers, randomly allocated to 3 groups of 6. Group 1 received 0.2 ml of distilled water. Group 2 and 3 animals were each given 0.2 ml of 40 mg/ml and 80 mg/ml TFS, respectively. The treatment was given orally once daily for 25 days. Assessment of HER2/neu and BCL2 expression was by immunohistochemistry, whereas BCV was measured by caliper. Anova and LSD were used for data analysis. RESULTS There was a significant difference in HER2/neu and BCL2 expression as well as in BCV among the treatment groups. LSD analysis showed that HER2/neu and BCL2 expression in group 3 (51.60%; 24.60%) was significantly lower than in group 1 (245.40%; 114.40%) as well as group 2 (235.50%; 54.20%) (p=0.000). BCV in group 3 (4392.33 mm3) was significantly greater than BCV in group 1 (253.87 mm3) (p=0.002), but was not significantly different from BCV in group 2 (3667.16 mm3) (p=0.306). CONCLUSION Suplementation with TFS decreases HER2/neu and BCL2 expression. TF appears to be a promising plant demonstarting anti cancer activity.